THE EFFECTIVENESS OF FILM THERAPY IN INCREASING EMPATHY FOR STUDENTS OF UIN RADEN FATAH PALEMBANG - Afilda Salsabila; Nabilla Almas Zakiyyah; Wijaya, Anggik; M Ridwan Maulana; Akhlul aqdi (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2022)
As a social being one form of caring for others is empathy. It is not uncommon in today's world for young people to lack empathy for each other and therefore do research to see a person's empathy by using experimental research that uses film therapy asa form of treatment from this study. The study is also aimed at seeing the effectiveness of film therapy in improving the empathy of university psychology student uin raden fatah palembang. The method of research in this study uses experimentation, using an observational sampling technique. The research sample of 30 students in uin raden fatah palembang. The design used was non-randomized the pre-testing posttest control design group. The data was analyzed using a SPSS test with an enhanced sample of the test that a 2-tailed value would be. 0044 > 0.05. Studies have shown that significant anatomas of film therapy are having a positive effect on a person's empathy. Thus, it may be concluded that the treatment given in the form of film therapy affects the empathy of the psychological student at the islamic university of raden fatah palembang from the pre-test and post-test experimental groups before and after it was given the "still Alice" movie